Implementasi Kebijakan Persetujuan Bangunan Gedung Di Kabupaten Parigi Moutong - Maharani, Dita; Riadi, Slamet; Tawil, Yulizar Pramudika (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
The implementation of the Building Approval policy in Parigi Moutong Regency still faces various challenges that affect the effectiveness of building permit services. This study aims to analyze the implementation of the Building Approval policy in Parigi Moutong Regency. The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The analysis is based on the policy implementation theory of Van Meter and Van Horn, which consists of policy standards and objectives, resources, characteristics of implementing agencies, interorganizational communication, implementer disposition, and social and economic conditions of the community. The findings indicate that the Building Approval policy has a clear legal basis, objectives, and implementation structure, namely to provide legal certainty, ensure conformity of development with spatial planning, and guarantee compliance with technical building standards. However, the implementation of the policy has not been fully optimal. The main obstacles identified include low levels of digital literacy among the community, limited policy socialization activities, insufficient human resources and supporting facilities, technical disruptions in the electronic licensing service system, and economic burdens experienced by the community. In addition, coordination among implementing agencies has been carried out but still encounters difficulties related to incomplete documentation and differing technical perceptions. Implementers generally demonstrate a supportive attitude toward the policy, although public complaints regarding service quality persist. This study concludes that the implementation of the Building Approval policy in Parigi Moutong Regency has not yet been fully effective and requires strengthening of human resource capacity, improved interagency coordination, and expanded policy socialization adjusted to local social and economic conditions.